PENGARUH KESEJAHTERAAN KARYAWAN, PENGEMBANGAN KARIR, DAN LINGKUNGAN KERJA TERHADAP RETENSI KARYAWAN - Anita Septiani; Muyasaroh; Ahlu Dzikri (STAI La Tansa Mashiro, 2026)
This study aims to analyze the effect of employee welfare, career development, and work environment on employee retention at PT Mahakarya Mitra Sejahtera. This research uses a quantitative approach with multiple linear regression analysis. Data were collected through questionnaires distributed to 80 respondents and processed using SPSS version 25. The results show that partially, employee welfare has a positive and significant effect on employee retention. Meanwhile, career development and work environment do not have a significant effect individually. However, simultaneously all independent variables have a significant effect on employee retention. The coefficient of determination (R²) is 0.177, indicating that the variables explain 17.7% of the variation in employee retention.